English Speaking Class in a Mathematics Program: Students’ Difficulties - Muhamad Holandyah; Kasinyo Harto; Ayu Mei Suli (Edukasi, 2022)
This is a qualitative research with a case study research design which aimed to find out the students’ difficulties in speaking at Non-English Speaking Class in Mathematics program study at UIN Raden Fatah Palembang. The researchers selected three students who met the criteria as a research participant by using criterion sampling. In collecting the data, the researchers used an interview as instrument. Thematic analysis was used to analyze the data. The result showed that the students faced some difficulties in speaking, such as lack of vocabulary, inhibition, mother-tongue use, and lack of confidence. The findings of the study encouraged students to practice speaking English more until they developed a speaking habit, which made them able to improve their speaking skills and also expanded their vocabulary better.